If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2l + 7) = 55 Reorder the terms: 5(7 + 2l) = 55 (7 * 5 + 2l * 5) = 55 (35 + 10l) = 55 Solving 35 + 10l = 55 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 10l = 55 + -35 Combine like terms: 35 + -35 = 0 0 + 10l = 55 + -35 10l = 55 + -35 Combine like terms: 55 + -35 = 20 10l = 20 Divide each side by '10'. l = 2 Simplifying l = 2
| 6z^2+7z+2=0 | | 9(x-2)=-3x+78 | | R=5x-16 | | .5555(9x+12)=10 | | 4-7(1-2v)=-33+8v | | p^2=2p+8 | | -x-2=-12 | | -30-5n=6(n+4) | | -9=117 | | .64x^2-6x-5000=0 | | 3(7X+8)=2(2x-4) | | p+3=80 | | -3x+9=6x+81 | | 3(3m-2)=3(m+3) | | 17x-(3x-6)=34 | | 110=10p | | 4a^5*ab= | | 64knots= | | 2x+x+x-6=36 | | (3w-7)(5w-8)=0 | | 432.94=220+0.78x | | -2-3m=-8 | | -8+21=m-1 | | 18x+14y=65 | | 14x^2y-35x=0 | | -6x+3(-4x+23)=-21 | | d-13=25 | | x-9=-1+7 | | -6x+3(-12x+23)=-21 | | 4x+24+3=-35 | | 4m-8=2m+8 | | -6x+10y=26 |